2020
DOI: 10.1088/1742-6596/1593/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

A new initial basis for the simplex method combined with the nonfeasible basis method

Abstract: The simplex method is a popular method to solve a linear programming problem. It starts by choosing an initial basis associated with the origin point which is far from the optimal point in some problems. In this paper, we introduce a construction of an initial basis for starting the simplex method associated with an extreme point which is close to the optimal solution. This construction involves the angle between the coefficient vector of the objective function and the coefficient vector of each constraint. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Hence, it is observed that Nabli and Chahdoura [27] (2015) method helps us to reduce the number of iterations as well as time. Finally, Sangngern and Boonperm [28] (2020) proposed another different way to handle the simplex method.…”
Section: Discuss Some Of the Recent Trends And Advancements In Simple...mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, it is observed that Nabli and Chahdoura [27] (2015) method helps us to reduce the number of iterations as well as time. Finally, Sangngern and Boonperm [28] (2020) proposed another different way to handle the simplex method.…”
Section: Discuss Some Of the Recent Trends And Advancements In Simple...mentioning
confidence: 99%
“…Sangngern and Boonperm [28](2020) developed a new simplex method with the initial basis, that considers the angle between the objective function coefficient vectors and each constraint. This method uses restrictions with modest angles to generate an initial basis close to the ideal answer.…”
Section: Discuss Some Of the Recent Trends And Advancements In Simple...mentioning
confidence: 99%
See 1 more Smart Citation
“…Some traditional methods are introduced, such as Largest Increase Rules, Steeps Edge rules [2] and Random Edge rules [3], to reduce steps. Recently, many latest revised methods are proposed, including Greatest Improvement Rule [4,5], Quick Simplex Method [6,7] and Three-Phase Method [8]. Thus, in this study, a variety of methods will be presented and evaluated.…”
Section: Introductionmentioning
confidence: 99%